How do Chinese Contractors Perform in Africa? Evidence from World Bank Projects - Jamie Farrell (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2016)
Chinese construction firms are building African infrastructure and have been winning large percentages of World Bank contracts in Africa. At the same time, many anecdotal media reports and some scholarly works portray the quality of Chinese construction in a negative light. This paper seeks to initiate a more evidence-based analysis of the quality of Chinese firms' construction work. The results indicate that Chinese firms performed similarly to OECD country firms on projects completed between 2000 and 2013; there are no statistically significant difference between their quality of work. The paper also examines possible underlying factors behind the negative perceptions of Chinese construction work, and it raises questions for further research.
Keywords: 330